CaRdiac Arrest Survival Score (CRASS) — A tool to predict good neurological outcome after out-of-hospital cardiac arrest. (1st January 2020) - Seewald, S.; Wnent, J.; Lefering, R.; Fischer, M.; Bohn, A.; Jantzen, T.; Brenner, S.; Masterson, S.; Bein, B.; Scholz, J.; Gräsner, J.T.
Abstract: Aim: The aim of this study was to develop a score to predict the outcome for patients brought to hospital following out-of-hospital cardiac arrest (OHCA). Methods: All patients recorded in the German Resuscitation Registry (GRR) who suffered OHCA 2010–2017, who had ROSC or ongoing CPR at hospital admission were included. The study population was divided into development (2010–2016: 7985) and validation dataset (2017: 1806). Binary logistic regression analysis was used to derive the score. The probability of hospital discharge with good neurological outcome was defined as 1/(1 + e −X ), where X is the weighted sum of independent variables. Results: The following variables were found to have a significant positive (+) or negative (−) impact: age 61–70 years (−0·5), 71–80 (−0·9), 81–90 (−1·3) and > = 91 (−2·3); initial PEA (−0·9) and asystole (−1·4); presumable trauma (−1·1); mechanical CPR (−0·3); application of adrenalin > 0 − < 2 mg (−1·1), 2 − <4 mg (−1·6), 4 − < 6 mg (−2·1), 6 − < 8 mg (−2·5) and > = 8 mg (−2·8); pre emergency status without previous disease (+0·5) or minor disease (+0·2); location at nursing home (−0·6), working place/school (+0·7), doctor's office (+0·7) and public place (+0·3); application of amiodarone (+0·4); hospital admission with ongoing CPR (−1·9) or normotension (+0·4); witnessed arrest (+0·6); time from collapse until start CPR 2 − < 10 min (−0·3) and > = 10 min (−0·5); duration of CPR <5 min (+0·6). The AUC in the development dataset was 0·88 (95% CI 0·87–0·89) and in the validation dataset 0·88 (95% CI 0·86–0·90). Conclusion: The CaRdiac Arrest Survival Score (CRASS) represents a tool for calculating the probability of survival with good neurological function for patients brought to hospital following OHCA.